Synthesis and Evaluation of Hermitamides A and B as Human Voltage-Gated Sodium Channel Blockers - De Oliveira, Eliseu O. (2011)
Hermitamides A and B are lipopeptides isolated from a Papau New Guinea collection of the marine cyanobacterium Lyngbya majuscula. We hypothesized that the hermitamides are ligands for the human voltage-gated sodium channel (hNa(V)) based on their structural similarity to the jamaicamides. Herein, we describe the nonracemic total synthesis of hermitamides A and B and their epimers. We report the ability of the hermitamides to displace [(3)H]-BTX at 10 μM more potently than phenytoin, a clinically used sodium channel blocker, a potential binding mode for (S)-hermitamide B in the BTX-binding site, and electrophysiology showing that these compounds are potent blockers of the hNav1.2 voltage-gated sodium channel.